Diplomasi Indonesia Menghadapi Kebijakan Renewable Energy Directive II (Pengembangan Energi Terbarukan) Uni Eropa Terhadap Ekspor Kelapa Sawit - Salman Muntaha; Hamka M (PT. Hasba Edukasi Mandiri, 2025)
Renewable Energy Directive II is a European Union policy designed to increase the use of renewable energy and reduce greenhouse gas emissions. The formation of RED II stems from the European Union's efforts to combat climate change, which began with the first Renewable Energy Directive (RED I) in 2009. This study aims to determine how Indonesian diplomacy in handling palm oil exports relates to the RED II policy issued by the European Union. This study uses Diplomacy Theory and National Interest Theory as well as the Concept of Renewable Energy. The research method used is a qualitative research method and the data collection techniques are derived from archives and Document-based Research and the internet. The conclusions generated from this study indicate that the RED II policy issued by the European Union greatly affects Indonesian palm oil exports due to several important elements related to the palm oil industry and crude palm oil (CPO) exports. The impact of the RED II policy affects the overall trade relationship between Indonesia and the European Union, the sectors involved in international trade, and reduces foreign investment and economic growth. The impact on labor and social welfare is also significant, as decreased production and exports could lead to mass layoffs and impact employment in related sectors such as transportation, logistics, and trade.